APLIKASI KONSELING BIBLIOTERAPI DENGAN MEDIA BUKU CERITA UNTUK MENGATASI KECEMASAN PADA ANAK DEMAN BERDARAH DENGUE (DBD) - Bassamah, Raafi’usan; Nuha, Moch. Syihabudin (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
Anxiety is a condition where a state of worry that complains that something bad is about to happen. Anxiety is normal, but it will become a new problem if it turns out to be in an excessive condition, so it requires help from professionals. Anxiety that occurs is caused by the first time entering the hospital and installing an IV in a child. The research method used was a qualitative approach with a case study. The results showed that there was a decrease in anxiety in the counselee, the counselee also regained his enthusiasm and wanted to recover and get out of the hospital.